An MDPSK homodyne receiver with adaptive phase-diversity. Issue 3 (6th February 2020) - Cao, Changqing; Wu, Zengyan; Zhang, Wenrui; Zeng, Xiaodong; Yan, Xu; Feng, Zhejun; Liu, Yutao; Wang, Bo
ABSTRACT: We propose an adaptive phase-diversity method for optical M-ary differential phase-shift keying (MDPSK) homodyne receivers, to achieve coherent optical communication. This method involves eliminating the random fluctuations in the phase differences between the signal light and local oscillator and the in-plane and quadrature signal (IQ) imbalance compensation. For the former, a phase-diversity method, which can theoretically eliminate all phase-related noise, is proposed. The gain and phase imbalances between the I and Q channels can be compensated completely by using automatic phase- and gain-control systems. The core idea is the adaptability of the receiver to the local phase shift of the local oscillator. The performance of the receiver is not sensitive to environmental factors such as temperature and vibrations. Our simulation results show that the imbalances between the IQ channels can be completely compensated over a wide imbalance range, and the baseband signals can be accurately recovered using the proposed scheme.